Hierarchy of hazard control to minimize lightning risk - Gomes, Ashen; Gomes, Chandima (IEEE (IEEE Xplore), 2014)
This paper presents analysis of various potential lightning risk scenarios, especially in less developed communities. We identify that there is no uniform safety promotion module that may be applicable to all communities with success. Hence we develop a hierarchy of hazard control mechanism that may be applicable to any given community with uniform professional or social practices. The hierarchy of control ladder has been integrated with the responsibility distribution network that runs from government level to the potential victim. The mechanism could be adopted by designers of lightning safety promotional programs in many parts of the world by appropriately determining the tools of implementation at various societal and professional levels. It is expected to minimize deaths and injuries as well as property damage due to lightning in vulnerable parts of the world.